Disruptive and Familiar Futures of Experiential Learning Theory and High Impact Practices : Synthesizing and building on current schools of thought. - Heinrich, Bill (Experiential Learning and Teaching in Higher Education, 2024)
This essay responds to and extends an interview with David Kolb, Alice Kolb, and George Kuh who discussed their definitions, research, and foundations of Experiential Learning Theory and High Impact Practices. I describe how the profound influence of ELT and HIPs have effectively disrupted higher education. I observed that institutions are operationalizing ELT and HIPs at an increasing pace without an updated, shared definition, leaving space for a collective agenda to emerge. I conclude with a call for further engagement with key questions and for scholars and practitioners to build the agenda of experiential and engage learning in meaningful and sustainable ways.